PENGARUH KOMBINASI POSISI POSTURAL DRAINASE DAN BATUK EFEKTIF TERHADAP PENGELUARAN SPUTUM DAN BERSIHAN JALAN NAFAS PADA PASIEN ASMA BRONKIAL DI RUANG BROMO RSUD GRATI PASURUAN - Andini Purwaningsih; Tri Nataliswati; Sulastyawati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Bronchial asthma is a condition where the occurrence of mucus hypersecretion, narrowing of the airway. Symptoms of bronchial asthma apart from shortness of breath accompanied by a wheezing sound, bronchial asthma sufferers also experience a productive cough because the sputum is thick and difficult to remove. There are two simple and easy therapies to treat bronchial asthma in sputum removal and airway cleaning, namely the postural drainage position and effective cough. The aim of this study was to determine the effect of the combination of postural drainage and effective coughing on sputum removal and airway clearance in patients. bronchial asthma. The design of this study used a pre-experimental design with one group pretest-posttest design with accidental sampling technique, the number of samples taken was 18 respondents. The results of the study after the intervention p-value 0.000 <Î± = 0.05, which means that there is an effect of a combination of postural drainage position and effective cough on sputum removal and airway clearance in patients with bronchial asthma. bronchial asthma patients. From the results of this study, it is hoped that nurses will refer to them to provide effective postural drainage and cough position interventions to help expel sputum and clear airways in bronchial asthma patients. And suggestions for bronchial asthma respondents can apply and share information to their closest family and the surrounding community to use these two therapies routinely at home independently